By the Honourable Spencer Phips, Esq ; lieutenant governour and commander in chief, in and over HIs Majesty's province of the Massachusetts-Bay in New-England. A proclamation for a general fast : ... Thursday the twenty-first of March next ... Given at the Council-chamber in Boston, the twenty-seventh day of February 1750 [1751 N.S.] . (Printed by John Draper, printer to His Honour the lieutenant-governour and Council, 1751)
February 27, 1750 Proclamation by Governor Spencer Phips to observe a day of general fasting and prayer on March 21st for God's support of the king and the continued Protestant succession.